The effectiveness of percutaneous endoscopic lumbar discectomy combined with external lumbar drainage in the treatment of intervertebral infections - Huang, Qun; Gu, Qi; Song, Jincheng; Yan, Fei; Lin, XiaoLong (Frontiers in Surgery, 2022)
Abstract Objective: To analyze the effect of percutaneous endoscopic lumbar discectomy in treating lumbar intervertebral infections. Methods: A total of 13 patients with lumbar intervertebral infections who underwent percutaneous endoscopic lumbar discectomy combined with external drainage between November 2016 and December 2019 were enrolled in the present study. After the operation, sensitive antibiotics were used based on the results of the bacterial culture. If no pathogens were detected in the biopsy culture of the infected tissues, empirical antibiotics were administrated to these patients. The clinical efficacy was evaluated by using a visual analog scale (VAS), Japanese Orthopaedic Association (JOA), Oswestry Disability Index (ODI), and standard Macnab’s evaluation. Postoperative computed tomography (CT) and magnetic resonance imaging (MRI) were also used to evaluate clinical efficacy. Results: The follow-up time was 10 to 18 months, and the average time was (13.69 ± 2.63) months. Causative bacteria were isolated in 7 of 13 infected tissue biopsy cultures. Systemic antibiotics and anti-tuberculous chemotherapy were administered according to sensitivity studies for identified. There were no pathogens isolated from the other 6 patients. Empiric antibiotics were administrated in these patients. One week after the operation, WBC, a fractional fraction of medium granulocytes, ESR and CRP were significantly lower compared to before the operation (all P < 0. 05). At the last follow-up visit, the above-mentioned markers were all within normal range, which differed compared to the pre-operative data (P < 0. 05). The VAS and ODI of the patients at 1 week and 3 months after operation were significantly lower compared to preoperative data (all P < 0. 05). During the last follow-up visit, 7 patients were excellent, 5 were good, and 1 was poor according to standard Macnab’s evaluation. No serious complications were recorded. Conclusions: Percutaneous lumbar discectomy combined with external drainage resulted as an effective method for treating lumbar intervertebral infections and was associated with fewer injuries, less pain, low cost, and low recurrence rate.